Phyllochron variability and cutting management practices on the agronomic potential of sorghum - Diego de Oliveira Camera; Marcos Paulo Ludwig; Juliano Dalcin Martins; Jardel Henrique Kirchner; Maicon Sérgio Santos; Bruna de Villa (Colloquium Agrariae, 2023)
The phyllochron is an indispensable parameter associated with the potential production of sorghum. Accordingly, management practices applied directly in the sorghum crop, such as the cutting technique, provide the ability of plants to regrowth and reestablish the performance of vegetative and reproductive development of plants based on the stimulation of growth in the photosynthetically active area. Appropriately, the aim of this study was to evaluate the alterations in phyllochron and leaf emission rates expressed by the implementation of cutting management practices in sorghum plants from high and low-quality seeds. The study was performed in the experimental and didactic area of ​​the Federal Institute of Rio Grande do Sul (IFRS) – Ibirubá campus, Rio Grande do Sul, Brazil. The experimental design was completely randomized and the treatments were plants from higher (HQS) and lower (LQS) quality seeds and two-season crops (2015/16 and 2016/17) with eight replications. The mean phyllochron (°C day leaf-1), height (cm), main stem diameter (cm), number of nodes, dry mass (kg ha-1), and number of tillers were evaluated as a strategy to verify the performance of each treatment. Furthermore, meteorological data obtained from an automatic station was required to calculate phyllochron and evapotranspiration (ETc). Finally, this study indicated that the diameter of the stem and tillers is directly associated with the accumulation of a dry mass of the crop, based on the results of biomass productivity. Moreover, it was demonstrated that forage sorghum plants derived from HQS indicated a higher capacity to accumulate photoassimilates, stimulating the production of dry mass.